THE EFFECT OF CIBODAS BOTANICAL GARDEN OFFICIAL WEBSITE PUBLICITY ON DOMESTIC TOURISTS VISITING DECISIONS - Layung Paramesti Martha; Prasetyo Adinugroho; Qamila Arianti Luthfindani (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2022)
The research to identify the influence of the Cibodas Botanical Garden  official website publicity on the visiting decision to domestic tourist which describe  how publicity on the official website of Cibodas Botanical Garden and analyze the  influence of official website publicity with visit decision of Cibodas Botanical  Garden domestic tourist. The research are use one independent variable which is  official website publicity and the visiting decision of domestic tourist as dependent  variable. The research uses survey techniques, which means that all member of the  research population were able as research respondents with a total of 100 domestic  tourist Cibodas Botanical Garden. To collect the researchs data were used techniques  questionnaire, observation and documentation. There were two data analyze  techniques, descriptive statistics (table and percentage) and non-parametric statistics  (Simple Linear Regression, F-Test, T-Test, Coefficient of Determination). The results  shown that there was a significant influence between Cibodas Botanical Garden  official website publicity and visiting decision to domestic tourist which are 41  percent. Then the other 59 percent are influenced by the other factor.